2017
DOI: 10.20944/preprints201712.0088.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Energy Consumption Analysis of D2D Communication in 5G Systems: Latest Advances in 3GPP Standardization

Abstract: Device-to-device (D2D) communication is an essential part of the future fifth generation 9 (5G) system that can be seen as "network of networks", consisting of multiple seamlessly integrated

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
(2 reference statements)
0
2
0
Order By: Relevance
“…Data rate and power consumption tradeoff have been discussed e.g. in [10] [11]. Energy consumption analysis of device to device (D2D) communication in 5G systems was presented in [11] that used 3GPP LTE and WiFi models to analyze the power consumption of both the BS and the UE.…”
Section: B Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Data rate and power consumption tradeoff have been discussed e.g. in [10] [11]. Energy consumption analysis of device to device (D2D) communication in 5G systems was presented in [11] that used 3GPP LTE and WiFi models to analyze the power consumption of both the BS and the UE.…”
Section: B Related Workmentioning
confidence: 99%
“…in [10] [11]. Energy consumption analysis of device to device (D2D) communication in 5G systems was presented in [11] that used 3GPP LTE and WiFi models to analyze the power consumption of both the BS and the UE. It was found that the best option to save energy is to minimize the number of active interfaces and send the data with the maximum possible data rate.…”
Section: B Related Workmentioning
confidence: 99%